Multi Stakeholder Engagement in Indonesia Sustainable Palm Oil Governance - Heldi Yunan Ardian; Djuara P. Lubis; Pudji Muljono; Delima Hasri Azahari (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Natural resource management generally involves parties with conflicting interests and roles. The emergence of a negative issue on palm oil development in Indonesia heralded by NGOs and vegetable oil competitor countries, for some groups, is considered merely a trade war. The rapid development of Indonesia's oil palm has made this commodity a source of global vegetable oil as well as risen a controversy over its sustainability aspects covering environmental, socio-economic and health issues. The significant increase of palm oil research led to the need to enrich the study's discussion on the sustainability aspect and involved the participation of the related stakeholders. This study is an early stage of a research based on the environmental communication theory to identify the problems and analyze the stakeholders involved in palm oil governance in Indonesia by using stakeholder analysis tools. The methods of data collection in this study included literature review, text analysis, in-depth interviews as well as direct observations. The study finding shows that the Ministry of Agriculture as the main actor in palm oil governance in Indonesia is required to share its authority. This indicates that palm oil sustainability issue is not the responsibility of a particular ministry but has become a national issue that requires the participation and collaboration of all relevant stakeholders.